2021
DOI: 10.1007/s00455-021-10320-5
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing Exercise During Head and Neck Cancer Treatment: Results of a Randomized Trial

Abstract: The diagnosis and treatment of head and neck cancer (HNC) can have substantial impact on swallowing function, nutritional balance, physical function and quality of life (QoL). Early initiated swallowing exercises are hypothesized to improve swallowing function in HNC patients. The aim was to investigate the effects of swallowing exercises and progressive resistance training (PRT) during radiotherapy on swallowing function, physical function and QoL in patients with pharynx-, larynx-, oral cavity cancer or unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 35 publications
1
67
0
Order By: Relevance
“…Several studies have shown that pre-emptive counseling, early identification of impairments, and early targeted therapy can reduce physical and socioemotional related morbidity secondary to HNC treatment ( Dawson et al, 2019 ; Guru et al, 2012 ; Lydiatt, 2020 ; Sterba et al, 2019 ). Additionally, recent reports have identified meaningful benefits of PT and SLPT with regard to quality of life (QOL) ( Baudelet et al, 2020 ; Burgos-Mansilla et al, 2021 ; Chiu et al, 2021 ; Hajdú et al, 2022 ). Despite the abundance of data demonstrating the benefit of PT and SLPT, several new reports have identified low adherence rates as a key detractor from the expected positive effects ( Baudelet et al, 2020 ; Chee et al, 2021 ; Chiu et al, 2021 ).…”
mentioning
confidence: 99%
“…Several studies have shown that pre-emptive counseling, early identification of impairments, and early targeted therapy can reduce physical and socioemotional related morbidity secondary to HNC treatment ( Dawson et al, 2019 ; Guru et al, 2012 ; Lydiatt, 2020 ; Sterba et al, 2019 ). Additionally, recent reports have identified meaningful benefits of PT and SLPT with regard to quality of life (QOL) ( Baudelet et al, 2020 ; Burgos-Mansilla et al, 2021 ; Chiu et al, 2021 ; Hajdú et al, 2022 ). Despite the abundance of data demonstrating the benefit of PT and SLPT, several new reports have identified low adherence rates as a key detractor from the expected positive effects ( Baudelet et al, 2020 ; Chee et al, 2021 ; Chiu et al, 2021 ).…”
mentioning
confidence: 99%
“…The second strategy entails enhancing QoL through specific interventions. Recommended interventions include the provision of swallowing function training and oral health care training to reduce the severity of dysphagia [38,39], the substitution of saliva for mouthwash to reduce xerostomia [40], implementation of regular home nursing interventions to improve global health [41], implementation of nutrition support and head-and-neck rehabilitation exercise to ameliorate fatigue [42], implementation of psychological interventions (particularly cognitive behavioral therapy) to mitigate depression or anxiety [43], and implementation of transdisciplinary geriatric and palliative care interventions to enhance the QoL of older adults with cancer [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, dosimeter information is rarely used to direct dysphagia management [ 59 ] and may be important to guide future clinical protocols. New studies have emerged which focus on personalising interventions based on motivation, mental reserve, treatment toxicity and tumour site [ 13 , 60 ]. Individually tailored therapy programmes combine functional skills training with progressive resistance training based on clinical examination of swallowing function [ 61 ].…”
Section: Speech and Language Pathology Interventionsmentioning
confidence: 99%